Rapid categorization of human and ape faces in 9-month-old infants revealed by fast periodic visual stimulation - Peykarjou, Stefanie; Höhl, Stefanie; Pauen, Sabina (Scientific reports, 2017)
This study investigates categorization of human and ape faces in 9-month-olds using a Fast Periodic Visual Stimulation (FPVS) paradigm while measuring EEG. Categorization responses are elicited only if infants discriminate between different categories and generalize across exemplars within each category. In study 1, human or ape faces were presented as standard and deviant stimuli in upright and inverted trials. Upright ape faces presented among humans elicited strong categorization responses, whereas responses for upright human faces and for inverted ape faces were smaller. Deviant inverted human faces did not elicit categorization. Data were best explained by a model with main effects of species and orientation. However, variance of low-level image characteristics was higher for the ape than the human category. Variance was matched to replicate this finding in an independent sample (study 2). Both human and ape faces elicited categorization in upright and inverted conditions, but upright ape faces elicited the strongest responses. Again, data were best explained by a model of two main effects. These experiments demonstrate that 9-month-olds rapidly categorize faces, and unfamiliar faces presented among human faces elicit increased categorization responses. This likely reflects habituation for the familiar standard category, and stronger release for the unfamiliar category deviants.